Clinical Staging of Amyotrophic Lateral Sclerosis in Chinese Patients - Chen, Xueping; Wei, Qian-Qian; Chen, Yongping; Cao, Bei; Ou, RuWei; Hou, Yanbing; Yuan, Xiaoqin; Zhang, Lingyu; Liu, Hui; Shang, Huifang (Frontiers in Neurology, 2018)
Objective: It is important to explore the utility of clinical staging systems in the management of amyotrophic lateral sclerosis (ALS). Our aim was to assess the validity of King’s College in a Chinese ALS cohort, by evaluating the duration and informativeness of each stage and examining the association between stage and prognosis. Methods: From May 2008 to December 2016, patients with a likely diagnosis of ALS were registered. We prospectively assessed the progression of the patients through the stages and calculated the duration of each stage. Results: The median duration in Stage 1 was 12.00 months, Stage 2 7.50 months, Stage 3 6.50 months, and Stage 4 4.10 months. Subset analysis revealed that the spinal-onset and early-onset patients had a longer median time in Stage 1compared to bulbar-onset and late-onset patients, respectively. Riluzole treatment extended the durations of Stages 1 and 2, and the effect was maintained in patients with long-term use of riluzole (>6 months). Patients who initiated long-term riluzole therapy early, in Stage 1 or 2, had a longer Stage 2. Patients who received percutaneous gastrostomy endoscopy (PEG) or non-invasive positive-pressure ventilation (NIPPV) showed longer durations of Stage 4. The differences in survival time measured from each stage to death or censor date were significant. Conclusions: We validated the King’s College staging system in a Chinese population, and showed this system to be useful in clinical practice. Patients with bulbar-onset or an age of onset>45 years tended to have rapidly progressing ALS. Riluzole may be more effective when initiated in an early disease stage and continued long-term. PEG and NIPPV treatments can extend disease duration of Stage 4.